การมีส่วนร่วมทางการเมืองท้องถิ่นของประชาชน : ศึกษาเฉพาะกรณี ตำบลช้างเผือก อำเภอเมือง จังหวัดเชียงใหม่ - โพธิสุข, บุศรา (Ganesha Journal, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์ 1. เพื่อศึกษาการมีส่วนร่วมทางการเมืองท้องถิ่นของประชาชน 2. เพื่อเปรียบเทียบการมีส่วนร่วมทางการเมืองท้องถิ่นของประชาชน จำแนกตามปัจจัยส่วนบุคคล และปัจจัยทางสังคมและเศรษฐกิจ และ 3. เพื่อศึกษาปัญหา แนวทางแก้ไขปัญหาการมีส่วนร่วมทางการเมืองท้องถิ่นของประชาชน ตำบลช้างเผือก อำเภอเมือง จังหวัดเชียงใหม่ กลุ่มตัวอย่างที่ใช้ในการวิจัย จำนวน 383 คน สัมภาษณ์เชิงลึกลึก (In-depth interview) จำนวน 20 คน และสนทนากลุ่ม (focus group) ได้แบบสอบถามกลับคืนมา จำนวน 361 ชุด เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถามและแบบสัมภาษณ์ สถิติที่ใช้ในการวิจัย ได้แก่ ความถี่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน การทดสอบสมมติฐานด้วยการทดสอบค่าที (t-test) และค่าเอฟ (F-test) การวิเคราะห์ข้อมูลนำเสนอโดยการบรรยายวิเคราะห์เชิงเนื้อหา ผลการวิจัยพบว่า การมีส่วนร่วมทางการเมืองท้องถิ่นของประชาชนโดยภาพรวม อยู่ในระดับปานกลาง ค่าเฉลี่ย เท่ากับ 2.86 ซึ่งสามารถเรียงตามลำดับจากมากไปน้อยได้ดังนี้ ด้านหลักอปริหานิยธรรมส่งเสริมการมีส่วนร่วมอยู่ในระดับปานกลาง ค่าเฉลี่ย เท่ากับ 3.27 ด้านการร่วมรณรงค์การเมืองท้องถิ่นอยู่ในระดับปานกลาง ค่าเฉลี่ย เท่ากับ 2.86 ด้านการตัดสินใจทางการเมืองอยู่ในระดับปานกลาง ค่าเฉลี่ย เท่ากับ 2.72 และด้านการดำเนินการเลือกตั้ง อยู่ในระดับปานกลาง ค่าเฉลี่ย เท่ากับ 2.59 ตามลำดับ ผลการศึกษาการเปรียบเทียบการมีส่วนร่วมทางการเมืองท้องถิ่นของประชาชน จำแนกตามปัจจัยส่วนบุคคล พบว่า อายุ และการศึกษา ประชาชนมีส่วนร่วมทางการเมืองท้องถิ่นแตกต่างกัน ส่วนเพศ และสถานภาพ ประชาชนมีส่วนร่วมทางการเมืองท้องถิ่นไม่แตกต่างกัน เมื่อจำแนกตามปัจจัยทางสังคมและเศรษฐกิจ พบว่า อาชีพ รายได้ต่อเดือน และตำแหน่งหน้าที่ในชุมชน ประชาชนมีส่วนร่วมทางการเมืองท้องถิ่นแตกต่างกัน ปัญหา พบว่า ประชาชนยังมีการปลูกฝังในระบบอุปถัมภ์อยู่ มีการแบ่งกลุ่ม ไม่ค่อยมีส่วนร่วมทางการเมือง ส่วนใหญ่จะมีส่วนร่วมเฉพาะช่วงเลือกตั้ง และการประชาสัมพันธ์เลือกตั้งยังไม่ครอบคลุมพื้นที่ แนวทางแก้ไขปัญหา ควรปลูกฝังให้ประชาชนมีแนวคิดที่เป็นประชาธิปไตย ให้ตระหนักในการใช้สิทธิเลือกตั้งเพื่อสังคมและประโยชน์ของส่วนร่วม ควรมีการรณรงค์ให้ความเข้าใจต่อการมีส่วนร่วมทางการเมืองมากยิ่งขึ้น และควรประชาสัมพันธ์การเลือกตั้งให้ครอบคลุมพื้นที่ The Local Political Participation of the People: A Case Study of Tambon Chang Phueak, Muang District, Chiang Mai Province This research report has the following objectives: to study the local political participation of the people, to study the compare local political participation of the people, social and economic factors on the political participation, and to study the problems and solutions of political participation of the people in Tambon Chang Phueak, Chiang Mai Province. The sample used in this study totaling 383. 20 of them were in-depth interviewed. And focus group. 361 sets of questionnaires were returned. The tools in this research consisted of question airs and interview forms. Tools used to collect statistical data were used in this study were frequency, percentage, mean, standard deviation, and t-test and F-test provides data tables and lectures. The Results of the research were as follows : The Participation of people was in the middle level. When considering the order from highest to lowest was found that the APARIHANIYADHAMMA average of 3.27. Political participation overall. In practice a moderate average of 2.86, which can be sorted in descending order as follows. Jim Mora's main shopping fair promotes participation. In practice a moderate average of 3.27 of a local political campaign. In practice a moderate average of 2.86 on a political decision. In practice a moderate average of 2.72 and the implementation of the election. In practice a moderate average of 2.59 respectively. The study the compare local political participation of the people, social and economic factors on the political participation. By personal factors were age, education, and public opinion on the involvement of local political differences, gender and status of public opinion is no different. When classified by social and economic factors that occupation, monthly income. And the title role in the community Public opinion on the involvement of local political differences. Problems that people also are implanted in the foster system. A Segmentation Little Political Participation Most are engaged only during elections. PR election and also covers the area. Solutions Should instill in people the idea of democracy. To realize the benefit of society and the electorate to participate. There should be a campaign to understand the political participation even more. And should promote the election coverage.